2020
DOI: 10.1021/acs.jpcc.0c08364
|View full text |Cite
|
Sign up to set email alerts
|

ZrO2@Ag@SiO2 Sandwich Structure with High SERS Enhancement Effect and Stability

Abstract: The spectroscopy of surface-enhanced Raman scattering (SERS), with its high sensitivity and specific chemical fingerprinting, has received increasing attention. A stable substrate is extraordinarily important for the trace detection of the SERS technique, but the challenge of SERS substrate production with high stability and uniformity still imposes the unavoidable barriers. In this paper, we design a multilayer core−shell-nanostructured ZrO 2 @Ag@SiO 2 nanoparticle through liquid extraction. First, we regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Thus, the detection capability of the Ag@MIL-101(Cr) film substrate was up to 10 −11 M. The characteristic Raman peaks of 4-ATP were clearly visible and consistent with previous reports. 38,39 There are four major peaks at 1077, 1141, 1390, and 1434 cm −1 in the Raman peaks of 4-ATP, which have posed a multivariate computation problem and increased the difficulty of calculation. Thus, to ensure the calculation accuracy and simplicity, we have adopted the principal component analysis (PCA) method 40 to reduce dimension numbers of those multivariate variables, and credibility could be ensured.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the detection capability of the Ag@MIL-101(Cr) film substrate was up to 10 −11 M. The characteristic Raman peaks of 4-ATP were clearly visible and consistent with previous reports. 38,39 There are four major peaks at 1077, 1141, 1390, and 1434 cm −1 in the Raman peaks of 4-ATP, which have posed a multivariate computation problem and increased the difficulty of calculation. Thus, to ensure the calculation accuracy and simplicity, we have adopted the principal component analysis (PCA) method 40 to reduce dimension numbers of those multivariate variables, and credibility could be ensured.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Xu et al achieved a 3-fold higher SERS signal with a superhydrophobic substrate based on a silver nanoparticle coated zinc oxide nanorods array (Ag@ZnO) than that on the ordinary hydrophilic Ag@ZnO substrate due to the superhydrophobic condensation effect [ 252 ]. Another research carried out by Shi et al fabricated multilayer core−shell-nanostructured ZrO 2 @Ag@SiO 2 nanoparticles through liquid extraction for the detection of 4-aminothiophenol (4-ATP) and rhodamine 6G (R6G) at 785 nm excitation and demonstrated that zirconia film protects the silver nanoparticles from aggregation, improving the stability of the substrate [ 190 ]. The list of 11 studies for SERS non-noble metal substrates other than Al and Cu (e.g., Fe 3 O 4 @Au nanoshells, CoFe 2 O 4 @HNTs/AuNPs, Au-ZnO NRs, Au semishells on TiO 2 spheres, etc.)…”
Section: Other Metals and Alloysmentioning
confidence: 99%
“…The list of 11 studies for SERS non-noble metal substrates other than Al and Cu (e.g., Fe 3 O 4 @Au nanoshells, CoFe 2 O 4 @HNTs/AuNPs, Au-ZnO NRs, Au semishells on TiO 2 spheres, etc.) are summarized in Table 4 [ 182 , 183 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 252 ].…”
Section: Other Metals and Alloysmentioning
confidence: 99%
“…Hence, it is highly non‐trivial to confine Ag NCs in a stable nanospace for protecting them from complex environments, and meanwhile, avoiding the direct contact with analytes. Recently, Ag@SiO 2 [ 30 ] and SiO 2 @Ag@TiO 2 [ 31 ] core‐shell NCs have been prepared to confine the Ag NCs in a nanospace of chemically inert SiO 2 or TiO 2 shell for avoiding the direct contact between Ag core and analytes, further achieving reliable SERS detection of several biomolecules. However, these core‐shell NCs may suffer from harsh conditions like extremely acidic and high‐salt solutions.…”
Section: Background and Originality Contentmentioning
confidence: 99%